Analysis of Household Income and Food Security of Watermelon Farmers During The Covid-19 Pandemic in Lamongan Regency - Annisa Annisa; Berti Genia Dwi Saputri; Rosihan Asmara; Fahriyah Fahriyah; Nuhfil Hanani (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2022)
The Covid-19 pandemic has disrupted the Indonesian economy in almost all sectors, including the agricultural sector. The government's policy for large-scale social restrictions has an impact on farmers' household income because it disrupts the access to sales of agricultural products. The low household income reduced opportunities to meet the needs of good quality food consumption, making food security difficult to achieve. Food security is reflected in two indicators, the level of energy adequacy and the proportion of household food expenditure. The aim of this research are to analyze income, food security and determinant factor of food security. The research was conducted in Trosono Village, Sekaran District, Lamongan Regency. It analyzed household food security using the Jonnson and Toole model. Further, factors influencing food security were analyzed using multiple linear regression analysis. This research found that (1) the average income of watermelon farming reached IDR 23,496,465 per hectare. Additionally, the research revealed that (2) watermelon farming households fell into the vulnerable (46.5%), the secure (23.2%), the insecure (20.9%), and the less secure (9.3%) categories. Finally, it was found that (3) several variables, such as the number of family members, the head of the family's education, income, rice expenditure, and maternal education, had a significant effect on the energy adequacy rate. The study reccomends farmers to hold technology counseling to increase their income, also there is a need socialization about the importance of regulating balanced, nutritious, and diverse food consumption patterns to increase mother knowledge to improve the nutritional status of their families.